EVALUASI PEMBELAJARAN BERBASIS ISLAM KEMUHAMMADIYAHAN SEBAGAI INTERNALISASI PENGUATAN PENDIDIKAN KARAKTER SISWA DI SD MUHAMMADIYAH KOTA MALANG - Delora Jantung Amelia (Universitas Kanjuruhan Malang, 2018)
Facts in the field illustrate that there are educational practices currently undergoing change. The intended change is the implementation of learning by integrating character education. This is in the background by the occurrence of a crisis of character and character of the younger generation, especially students in school. Character education leads to the exemplary practice of every stakeholder in the school. Stake holder has a great contribution not only as a practitioner of education, but also as the spearhead of the successful application of character education for students. To realize the implementation of character education in schools, one of them is the application of full day school learning. This study describes the implementation of evaluation of Islam-based learning later as an effort to strengthen character education in schools. The procedure of this research is by observing the activities of the teacher and students when learning takes place and then analyzing whether the implementation of evaluation in student-based learning is able to foster student character education. Most of the implementation activities of Islamic learning activities at the Muhammadiyah 9 elementary school in Malang are in accordance with the 2013 curriculum implementation standard. The implementation of Islamic learning activities has a supporting factor and inhibitor which all inhibiting factors can be overcome properly